Building inclusive financial systems a framework for financial access - Barr, Michael S.; Kumar, Anjali; Litan, Robert E., 1950- (Emerging markets series., 2007)
"Addresses the challenges of making financial systems more inclusive, emulating successful ventures in new markets, and utilizing technologies and government policies to support the expansion of financial access. Examines many dimensions of financial access, including measuring financial access, understanding the impact of expanded access, and examining alternative institutional models"--Provided by publisher.